The rainmaker?! The impact of investors on transfer fees in the English Premier League - Lukas Richau; Florian Follert; Monika Frenger; Eike Emrich (Helmut-Schmidt-Universität - Universität der Bundeswehr Hamburg, Fächergruppe Volkswirtschaftslehre, 2021)
Transfer fees in European football have experienced a rapid increase in the past years. Simultaneously, an increasing number of domestic and recently foreign investors - who are assumed to further increase team spending in European football - have entered the football market by becoming club owners. In light of these developments, fears associated with an increasing influence of foreign (majority) investors from the financial as well as the emotional fan perspective have increased. Given the rather limited number of empirical studies focusing on the impact of investors on transfer fees, we shed further light on this topic. Based on a data sample from 2012/13 to 2018/19 for the English Premier League, we estimate OLS regressions and quantile regressions to analyze the effects of ownership concentration and investor origin on the amount of individual transfer fees. While we do not find strong evidence that ownership concentration increases the willingness to pay, we find fairly consistent results that foreign investors are willing to pay a premium compared to domestic investors. Our results also indicate that especially foreign investors who own a majority share of a club have a positive effect on transfer fees for the upper quantiles.
Keywords: D23; G32; Z22; Z23; 330; Sports finance; property rights; club ownership; investors; football transfer market